2019
DOI: 10.3390/nu11122964
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Omega-3 Fatty Acid Composition Is Associated with Infant Temperament

Abstract: There is growing evidence that omega-3 (n-3) polyunsaturated fatty-acids (PUFAs) are important for the brain development in childhood and are necessary for an optimal health in adults. However, there have been no studies examining how the n-3 PUFA composition of human milk influences infant behavior or temperament. To fill this knowledge gap, 52 breastfeeding mothers provided milk samples at 3 months postpartum and completed the Infant Behavior Questionnaire (IBQ-R), a widely used parent-report measure of infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
0
16
2
Order By: Relevance
“…In addition, recent studies have shown a correlation between maternal perinatal psychopathologies, such as depression, anxiety, stress, and human milk composition in terms of macronutrients and immune components, immunoglobulin A, hormones, and cortisol. Some recent studies has shown that lower levels of DHA in breast milk were found in those countries where the prevalence of maternal depression was higher, impairing the adequate neurodevelopment of the offspring [ 45 ].…”
Section: Nutrition During Pregnancy and Lactationmentioning
confidence: 99%
“…In addition, recent studies have shown a correlation between maternal perinatal psychopathologies, such as depression, anxiety, stress, and human milk composition in terms of macronutrients and immune components, immunoglobulin A, hormones, and cortisol. Some recent studies has shown that lower levels of DHA in breast milk were found in those countries where the prevalence of maternal depression was higher, impairing the adequate neurodevelopment of the offspring [ 45 ].…”
Section: Nutrition During Pregnancy and Lactationmentioning
confidence: 99%
“…There are several studies, however, that demonstrate the involvement of both ω-3 fatty acids and oxytocin in development. For example, higher levels of ω-3 fatty acids in maternal milk are associated with better temperament in children [157], and reduce negative affect and inflammation in children that have mothers with high levels of adiposity [158], while lower levels of oxytocin have been related to experiences of severe emotional neglect and abuse in childhood in plasma and cerebrospinal fluid samples [159,160]. Children raised in orphanages who experienced neglect have also been shown to have lower oxytocin plasma levels [161].…”
Section: Early-life Stress and Microglia: Clinical Studiesmentioning
confidence: 99%
“…It has been reported that sphingomyelin lipids (which contain high amounts of C16:1, C18:1n11, and long-chain fatty acids) were significantly higher in the brain tissues of recently weaned rats fed with human milk or infant formula (6) . Hahn-Holbrook et al (7) observed decreased sadness and distress in babies after human milk intake, attributed to its high concentration of n-3 PUFAs. The authors also linked human milk cholesterol to brain maturation (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Hahn-Holbrook et al (7) observed decreased sadness and distress in babies after human milk intake, attributed to its high concentration of n-3 PUFAs. The authors also linked human milk cholesterol to brain maturation (7) . Moreover, according to Isaacs et al (8) , human milk consumption affects white matter and cognition by increasing glial myelination.…”
Section: Introductionmentioning
confidence: 99%